2022
DOI: 10.1001/jamasurg.2022.3687
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities and Health Disparities for Advance Care Planning Before Elective Surgery in Older Adults

Abstract: ImportanceAdvance care planning (ACP) prepares patients and caregivers for medical decision-making, yet it is underused in the perioperative surgical setting, particularly among older adults undergoing high-risk procedures who are at risk for postoperative complications. It is unknown what patient factors are associated with perioperative ACP documentation among older surgical patients.ObjectiveTo assess ACP documentation among high-risk patients 65 years and older undergoing elective surgery.Design, Setting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Participation led to an examination of our own performance on the metric and demonstrated that less than 15% of older adult patients undergoing major elective surgery had ACP documentation in the metric-defined 90-day presurgery window . 7 Furthermore, these data showed disparities in rates of ACP, with it being particularly uncommon in men and individuals who prefer a non-English language.…”
Section: Problem Detailingmentioning
confidence: 87%
“…Participation led to an examination of our own performance on the metric and demonstrated that less than 15% of older adult patients undergoing major elective surgery had ACP documentation in the metric-defined 90-day presurgery window . 7 Furthermore, these data showed disparities in rates of ACP, with it being particularly uncommon in men and individuals who prefer a non-English language.…”
Section: Problem Detailingmentioning
confidence: 87%
“…Similar to prior work among elective surgical patients, we show that patients with higher odds of having ACP documentation tended to be older, prefer English, and possess government-funded health insurance. 14,19 While Medicare insurance may be a proxy for older age, which was also predictive of ACP documentation, funding structures such as reimbursement for ACP conducted during annual wellness visits, which began in 2016 have also been associated with an overall increase in ACP. 20 Importantly, however, as part of this reimbursement structure, only ACP conversations conducted as part of an annual wellness visit are protected from additional out-of-pocket patient costs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Black, Hispanic, and Medicaid dual-eligible patients and patients with comorbidities are less likely to have annual wellness visits and also less likely to have ACP billed as part of one of these visits. Non-English preferred language is known to be a significant barrier to ACP among surgical patients, 14 and several factors likely contribute to these differences, including cultural norms and patient preferences, yet lack of access to high-quality language-concordant ACP continues to be demonstrated across clinical contexts 21 . For example, among 18,490 seriously ill older adults, patients with non-English preferred language had higher end-of life health care utilization (higher odds of emergency department visits, readmission, in-hospital death) but were less likely to have ACP documents 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colley et al report sobering data that highlight a series of missed opportunities for advance care planning (ACP). Despite allowing ACP documentation within a generous 90-day preoperative window, the authors found that less than 15% of older patients (age ≥65 years) undergoing inpatient elective surgery had ACP documentation, and only 19.5% of patients who were admitted to the intensive care unit had this documentation.…”
mentioning
confidence: 81%